(untitled) (Al-Academy, 2019)
The research (Comic Scene Construction between Dramatic Situation and Acting Performance in Feature Film) has been divided into the following: the methodological framework which consists of the problem of the research: how to construct the comic scene between the dramatic situation and acting performance in the feature film. The research importance and aims are: identifying how to construct the comic scene between the dramatic situation and acting performance in the feature film. The limits of the research are also stated.The research is divided into three sections: the first is the comic situation and the Aristotelian discourse in which the comic situation is clarified starting from the Aristotelian discourse. The second section: mechanisms of acting. The third is: acting performance and the construction of the feature film which addressed the relationship between the acting performance and language elements. Then, the researcher came up with the indicators of the theoretical framework which will be used as a tool for analyzing the sample. The research procedures included the research methodology, tool, sample, analysis unit, validity and the research sample which is the Arabic film (8 Giga) directed by Ashraf Fayiq produced in 2010. The researcher analyzed the sample and came up with a number of results and conclusions and ended the research with a list of references